Caribbean trade and integration : trends and future prospects \n - Freckleton, Marie [et al] (UN ECLAC SantiagoCL, 2010)
Analyses recent trends and future prospects. Reviews the progress made with reforms to complete the CSME by 2015, concluding that important advances have been made towards this goal, but many obstacles remain.